Didactic Sequence of Modern Physics: Perceptions of Students on In-Service Science Teaching - Rodrigues Junior, Edmundo; Oliveira, Paulo José; Admiral, Tiago (Cadernos de Educação Tecnologia e Sociedade, 2022)
Physics taught in Brazil high school mostly prioritize topics related to classical mechanics, often not providing opportunities for understanding and discussing current topics of the students' living context. In this article, we show the result of a qualitative research conducted with thirteen students enrolled in a postgraduate course in natural science teaching in which the objective of the proposal was to develop, apply and evaluate a didactic sequence of modern physics based on the Instruction by Colleagues (IpC) methodology, but with some modifications. With some adaptations the didactic sequence can also be applied in high school. We chose modern and contemporary physics topics as a guiding theme for our analysis, believing that the teaching of this subject is still incipient in Brazil high schools. Eight classes we used totaling 30 hours. To analyze the data we used the technique of content analysis. The didactic sequence allowed the graduate students to judge the scenario of teaching modern physics, in addition to giving the teacher the opportunity to act as a mediator of knowledge, considering the answers provided by the students and prioritizing the evolution of the students' knowledge.<s></s>